2017
DOI: 10.1371/journal.pone.0179146
|View full text |Cite
|
Sign up to set email alerts
|

Serological signatures of declining exposure following intensification of integrated malaria control in two rural Senegalese communities

Abstract: Recent control scale-up has reduced malaria in many areas but new tools are needed to monitor further progress, including indicators of decreasing exposure to parasite infection. Although serology is considered a promising approach in this regard, the serological impact of control interventions has been so far studied using indirect quantification of exposure. Cohort surveys concomitantly recording entomological and malariometric indices have been conducted in two Senegalese settings where supervised control i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 63 publications
(170 reference statements)
1
42
0
Order By: Relevance
“…Similarly, higher seroprevalence and higher antibody titres were observed in children and adults immediately after the high‐transmission season (a period of intense exposure) relative to observed levels before the malaria season (a period of little to no transmission) 99. Two Senegalese studies also recently reported a decline in seroprevalence of antibodies to both pre‐erythrocytic and erythrocytic stage antigens in children, as the entomological inoculation rate (EIR) declined over the years 102, 103. Clearly, high exposure levels are associated with higher antibody levels, and children harbour higher parasitaemia before manifesting clinical symptoms 58, 61, 96.…”
Section: The Role Of Inflammation In Malarial Pathogenesismentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, higher seroprevalence and higher antibody titres were observed in children and adults immediately after the high‐transmission season (a period of intense exposure) relative to observed levels before the malaria season (a period of little to no transmission) 99. Two Senegalese studies also recently reported a decline in seroprevalence of antibodies to both pre‐erythrocytic and erythrocytic stage antigens in children, as the entomological inoculation rate (EIR) declined over the years 102, 103. Clearly, high exposure levels are associated with higher antibody levels, and children harbour higher parasitaemia before manifesting clinical symptoms 58, 61, 96.…”
Section: The Role Of Inflammation In Malarial Pathogenesismentioning
confidence: 96%
“…99 Two Senegalese studies also recently reported a decline in seroprevalence of antibodies to both pre-erythrocytic and erythrocytic stage antigens in children, as the entomological inoculation rate (EIR) declined over the years. 102,103 Clearly, high exposure levels are associated with higher antibody levels, and children harbour higher parasitaemia before manifesting clinical symptoms. 58,61,96 This observation, however, raises a question: how is it that highly exposed children from endemic areas are able to prevent aggravated immunopathology which should, supposedly, ensue from comparatively higher antigenaemia (parasitaemia)?…”
Section: The Role Of Inflammation In Malarial Pathogenesismentioning
confidence: 99%
“…The challenge lies in selecting appropriate biomarkers and choosing between the increasing number of commercial assays, many of which have not been extensively validated and may produce conflicting results. The opportunity is that with multiple biomarkers, it is possible to generate a serological signature of infection that is robust to how antibody levels change over time [17][18][19][20], rather than relying on classification of sero-positive individuals using a single cutoff antibody level.…”
Section: Introductionmentioning
confidence: 99%
“…before peak transmission in Dielmo (holoendemic area) and before the transmission season in Ndiop (meso-endemic). Overall 184 and 196 villagers in Dielmo, and 202 and 216 villagers in Ndiop were evaluated in 2002 and 2013, respectively with a sub-group of samples from 75 (Dielmo) and 86 (Ndiop) individuals who participated to both studies ( Table 2) [27]. After withdrawal, plasma and red blood cells were separated by centrifugation and stored at − 20 °C.…”
Section: Table 1 Characteristics Of Recruitment Of Patients and Indivmentioning
confidence: 99%
“…In this report, a practical example is provided as a snapshot cross-sectional picture using samples from symptomatic and asymptomatic cohorts in the Côte d'Ivoire and Senegal. A large panel of antigens were initially explored using the multiplex Luminex assay [25][26][27], here analysis was focused on 3 main antigen targets: (i) a preerythrocytic antigen LSA1 41 ; (ii) a merozoite antigen MSP1p19, and (iii) a whole schizont extract (SE: measured by standard ELISA) from a local strain adapted to in vitro culture [28], as a reference antigen for overall antibody response against P. falciparum. In the cohort from Senegal, antibody responses to six additional antigens are given with regards to the sero-catalytic models.…”
Section: Introductionmentioning
confidence: 99%